2002
DOI: 10.1016/s0002-9440(10)62577-1
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Gene Transfer Sensitizes Melanoma Cells to Apoptosis via a Target Activity on Mitochondrial Function

Abstract: Our previous article reported that retroviral transduction of human type I consensus interferon-coding sequence into two human melanoma cells increased their susceptibility to cisplatin-induced apoptosis. Importantly, primary melanoma cells were significantly more sensitive to cisplatin-induced apoptosis with respect to metastatic melanoma cells. The aim of this study was to elucidate the subcellular mechanisms involved in this interferon-induced apoptotic proneness. Our results indicate that 1) cisplatin-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…JC-1, a very sensitive reagent largely used to evaluate MMP changes occurring in apoptosis, allows the measurement of both the earlier events (i.e. hyperpolarization) (22) and later events (i.e. depolarization) (18) state of mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…JC-1, a very sensitive reagent largely used to evaluate MMP changes occurring in apoptosis, allows the measurement of both the earlier events (i.e. hyperpolarization) (22) and later events (i.e. depolarization) (18) state of mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Human metastatic melanoma cell lines 8863 and 501 have been previously described (10,18). These cell lines were cultured in RPMI 1640 (Life Technologies, Invitrogen) supplemented with 10% heat-inactivated fetal bovine serum (Euroclone), 2 mmol/L glutamine (Sigma), and 50 Ag/mL gentamicin (Sigma).…”
Section: Cell Linesmentioning
confidence: 99%
“…The expression and the activation state of cathepsin B was evaluated by both flow cytometry and Western blot, as previously described (10). For details, see Supplementary Materials and Methods.…”
Section: Analytic Cytology Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Type I IFNs also directly inhibit proliferation of neoplastic cells through various mechanisms including induction of apoptotic cell death. [10][11][12][13] It has also been reported that activation of DCs with IFN-a or -b leads to upregulation of TNF-a-related apoptosis-inducing ligand (TRAIL) expression, and to direct tumoricidal activity mediated by DCs via TRAIL. 14,15 IFN-a-transduced tumor cells also activate and promote the survival of tumor-specific CD8 + CTLs in vivo.…”
Section: Introductionmentioning
confidence: 99%